Efectos económicos de la deserción en la gestión universitaria: el caso de una universidad pública chilena (2020)
Dropout is a reality for universities around the world, especially in Latin America. Dropout causes losses of resources that are difficult to quantify, especially for universities, whose financial management depend largely on income from their undergraduate careers, where this phenomenon is a fact, without there being a measure of assessment of the economic effects it creates for each institution. In this context, the aim is to quantify the dropout costs from a Chilean state university, based on its academic and financial data, between 2016 and 2019. A dropout of 2900 students was observed in the period, which represents a 7.67% average of dropout regarding the total enrollment. The main reason for dropping out is the loss of career associated with academic performance and the fact that most of the students who dropped out had free scholarship as source of funding, which represents a high cost for the State. In monetary terms, dropout cost by 2019 amounts to USD 23 428 287.14.